2022
DOI: 10.1039/d1cp04951h
|View full text |Cite
|
Sign up to set email alerts
|

Improved highly efficient Dion–Jacobson type perovskite light-emitting diodes by effective surface polarization architecture

Abstract: Quasi-two-dimensional (quasi-2D) perovskites are emerging as promising materials for high stable light-emitting diodes (LEDs). However, their lower charge transport mobilities and higher defects may constrain light-emitting efficiencies. Here, we combine...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 42 publications
(63 reference statements)
0
4
0
Order By: Relevance
“…However, progress in their LED applications has been slower compared to solar cells, which is not entirely unexpected since these materials are more recent, and their efficiency still lags behind record results of RP perovskite LEDs. Nevertheless, DJ perovskite LEDs emitting in near-infrared (NIR), ,, green, ,, and blue , spectral ranges have been reported, with reported efficiencies in the blue spectral range of 2.65% and 8.5%, while for the green spectral range wider ranging values were reported, such as 1.06%, 8.5%, 10.5%, 12.85, and 17.1% …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, progress in their LED applications has been slower compared to solar cells, which is not entirely unexpected since these materials are more recent, and their efficiency still lags behind record results of RP perovskite LEDs. Nevertheless, DJ perovskite LEDs emitting in near-infrared (NIR), ,, green, ,, and blue , spectral ranges have been reported, with reported efficiencies in the blue spectral range of 2.65% and 8.5%, while for the green spectral range wider ranging values were reported, such as 1.06%, 8.5%, 10.5%, 12.85, and 17.1% …”
Section: Introductionmentioning
confidence: 99%
“…However, progress in their LED applications has been slower compared to solar cells, which is not entirely unexpected since these materials are more recent, and their efficiency still lags behind record results of RP perovskite LEDs. Nevertheless, DJ perovskite LEDs emitting in near-infrared (NIR), 5,11,13 green, [6][7][8]12,14 and blue 9,10 spectral ranges have been reported, with reported efficiencies in the blue spectral range of 2.65% 10 and 8.5%, 9 while for the green spectral range wider ranging values were reported, such as 1.06%, 7 8.5%, 14 10.5%, 12 12.85, 8 and 17.1%. 6 While their structure (stronger bonding and shorter interlayer spacing) is expected to result in increased stability 2 and direct comparisons of RP and DJ perovskite-based LEDs indeed confirmed stability advantage of DJ LEDs, 5 the stability advantage, if any, is less clear for the devices operating in the visible spectral range.…”
Section: ■ Introductionmentioning
confidence: 99%
“…11,23,24 Expected improved stability makes DJ perovskites particularly interesting for practical applications, but they have been less commonly studied compared to RP perovskites. 22,25–32 Several works in the literature involve combinations of monovalent and divalent bulky cations, 9,31 or the use of diammonium cations for passivation, 26 while the reports on pure DJ phase perovskites using only divalent spacer cations remain scarce. 22,27–30,32 The scarcity of reports on DJ perovskite PeLEDs could partly occur due to differences in the formation enthalpies for quasi-2D RP and DJ perovskites.…”
Section: Introductionmentioning
confidence: 99%
“…22,25–32 Several works in the literature involve combinations of monovalent and divalent bulky cations, 9,31 or the use of diammonium cations for passivation, 26 while the reports on pure DJ phase perovskites using only divalent spacer cations remain scarce. 22,27–30,32 The scarcity of reports on DJ perovskite PeLEDs could partly occur due to differences in the formation enthalpies for quasi-2D RP and DJ perovskites. 24 It was reported that DJ perovskites exhibit positive formation enthalpies, which makes them metastable.…”
Section: Introductionmentioning
confidence: 99%